2005
DOI: 10.1001/jama.294.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Risk of Type 2 Diabetes

Abstract: Context Emerging epidemiological evidence suggests that higher coffee consumption may reduce the risk of type 2 diabetes.Objective To examine the association between habitual coffee consumption and risk of type 2 diabetes and related outcomes. Data Sources and Study SelectionWe searched MEDLINE through January 2005 and examined the reference lists of the retrieved articles. Because this review focuses on studies of habitual coffee consumption and risk of type 2 diabetes, we excluded studies of type 1 diabetes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
371
5
17

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 607 publications
(423 citation statements)
references
References 59 publications
30
371
5
17
Order By: Relevance
“…Coffee and tea consumption may affect serum uric acid levels via various mechanisms including influence on insulin resistance (2)(3)(4)(5)(6)(7)(8)(9), but few data are available. Only 1 cross-sectional study investigated the link between these beverages and serum uric acid level based on 2,240 Japanese men and found a significant inverse association between coffee consumption and serum uric acid levels but no association with tea consumption (10).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coffee and tea consumption may affect serum uric acid levels via various mechanisms including influence on insulin resistance (2)(3)(4)(5)(6)(7)(8)(9), but few data are available. Only 1 cross-sectional study investigated the link between these beverages and serum uric acid level based on 2,240 Japanese men and found a significant inverse association between coffee consumption and serum uric acid levels but no association with tea consumption (10).…”
Section: Introductionmentioning
confidence: 99%
“…Coffee is the major source of the phenol chlorogenic acid, which is a strong antioxidant (8,30). Previous studies have suggested that plasma glucose concentrations are reduced by chlorogenic acid (30,31), which may combine with other antioxidants in coffee to decrease oxidative stress.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9 Tsioufis et al 10 demonstrated an association between heavy coffee consumption (44 cups/day) and inflammatory processes in a small sample of Greek hypertensive smokers, which was supported by cross-sectional findings from a larger study of over 3000 healthy Greek men and women. 11 In contrast, other recent reports suggest that coffee has anti-oxidant properties 12 and ingredients such as flavonoids, potassium, magnesium and chlorogenic acid that could exert anti-inflammatory effects and lower the risk of type II diabetes 13 and other inflammatory diseases. 14 Other studies have used direct measures of vascular function.…”
mentioning
confidence: 91%